PEMANFAATAN PEPAYA DENGAN TEKNOLOGI PANGAN DAN PENGELOLAAN MANAJEMEN KEUANGAN SEBAGAI WUJUD OPTIMALISASI PEREKONOMIAN KELUARGA DI DESA SIDOMULYO - Astrid Maharani; Retno Murwanti; Alivia Dewi Sandra; Hikmatus Syarifah (JURNAL PENGABDIAN MANDIRI, 2022)
It is hoped that the community service program will eventually create a public awareness to develop various kinds of processed fruit from papaya, so that it can add economic value and be useful in improving the economy of women in the Sidomulyo Village Family Welfare Empowerment Group. The method used in this Community Service activity is to use the method of counseling and discussing the benefits of papaya for health and family nutrition, technical methods of making papaya sauce and explaining how business and marketing analysis of papaya sauce becomes a competitive product. Thus, it is hoped that there will be a synergy between community service programs, university strategic plans, and local government programs by optimizing the use of papaya as a processed product of high economic value and worth.